ANALISIS PERILAKU KONSUMEN PADA REPEAT PURCHASE DECISION DALAM TRANSAKSI DI E-COMMERCE (STUDI PADA KONSUMEN TOKOPEDIA) - Erwin Timoty Parluhutan Purba (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This research explores the behavior and decision-making process of consumers when they make purchases in the E-commerce industry. The primary objective of this thesis is to focus on understanding the underlying reasons why consumers buy certain products, how much they are willing to pay for them as well as the impact of content marketing on consumer engagement, customer loyalty and what factors influence their purchasing decisions In Tokopedia, one of Indonesia's top e-commerce platforms through a quantitative survey of Tokopedia users. The research methodology involved a quantitative approach, with a survey distributed to 100 Tokopedia customers who have experienced content marketing activities with a Likert scale of 1-4. The research contributes to the understanding of content marketing effectiveness in the e-commerce industry and provides insights for practitioners to develop effective marketing strategies. According to the research, content marketing boosts repeat purchase behavior by favorably influencing consumer engagement and loyalty. The study also gives a framework for evaluating the efficacy of content marketing and determines the content kinds that Tokopedia's users respond to the best.